Handling Former Terrorist Convict in Cirebon Region: Analysis of Collaborative Governance - Tando, Cahyoko Edi; Bifri, Vivi Sylivani; Aulia, Qisthina (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
The case of former Terrorism Convicts has had almost minimal review due to the lack of scientific power to develop concepts in this case. Through analysis of the Collaborative Governance theory. This research uses qualitative methods. The results of the research show that with the collaborative governance analysis, various actions have been carried out, including collaboration between agencies carried out through joint decrees. Then there is an important role at the Cirebon Class 1 Correctional Center (Bapas), providing guidance because the majority of former terrorist convicts are on parole and are required to report every month. The Idensos Team's next role is to provide support through various efforts, for example fully supporting and assisting them in entrepreneurship to achieve a level of economic independence. The involvement of private actors through PT Syang Hyang Seri where they provide assistance in agricultural extension in collaboration with former terrorist convicts in the Cirebon area, as a form of de-redicalization. Meanwhile, changes in community stigma were carried out by involving Bapas officers, then village heads, to support social reintegration. The limitations of this research are only in the context of the Cirebon region and the use of qualitative research methods. So it cannot explain the percentage contribution of each actor.